Waist circumference and waist-hip ratio as screening tools for hypertension in children aged 6–11 years - Esti Istiqomah; Dida A. Gurnida; Dany Hilmanto; Dzulfikar Djalil Lukmanul Hakim; Prima Nanda Fauziah (Paediatrica Indonesiana, 2019)
Background Hypertension in children is associated with obesity. 7 The renin-angiotensin-aldosterone system has been associated with intra-abdominal fat tissue. Anthropometric parameters for determining nutritional status include waist circumference and waist-hip ratio. Many studies have shown that waist circumference and waist-hip ratio are more precise to determine overweight or obese. Objective To determine the usefulness of waist circumference and waist-hip ratio as hypertensive screening tools for children aged 6-11 years. Methods This analytical study with cross-sectional design and multistage cluster sampling method was conducted in August-September 2017 at a primary school in Bandung, West Java, Indonesia. Subjects underwent height, weight, waist circumference, hip circumference, and blood pressure measurements. Receiver operating characteristic (ROC) curve analysis was done to obtain the area under curve (AUC), cut-off point, sensitivity, specificity, and prevalence ratio. Results Subjects were 325 children consisting of 187 males and 138 females. Hypertension was diagnosed in 47 children (37 males and 10 females). Mean waist circumference and waist-hip circumference ratio were significantly higher in the hypertensive group than in the normotensive group. The hypertensive group had a mean waist circumference of 72.6 (SD 12.8) cm, AUC 0.779 (95%CI 0.730 to 0.823; P<0.001), cut-off point >65 cm, sensitivity 66.0%, specificity 76.3%, and prevalence ratio 4.55. This group had mean waist-hip ratio of 0.94 (SD 0.10), AUC 0.724 (95%CI 0.672 to 0.772; P<0.001), waist-hip ratio cut-off >0.91, sensitivity 59.6%, specificity 77.0%, and prevalence ratio 3.73. Conclusion Waist circumference >65 cm or waist-hip ratio >0.91 can be used to screen for hypertension in children aged 6-11 years with negative predictive values of 92.0% and 91.8%, respectively.